Blood donation in China from 2017 to 2021: A cross-sectional study - Jing Wang; Xinyao Pan; Jing Zhou; Ling Wang (World Scientific Publishing, 2023)
Objective: The objective of this cross-sectional study is to examine the essential demographic characteristics of blood donors in China from 2017 to 2021 and to analyze the impact of various factors on blood donation in China, including the blood donor's attitudes towards family replacement/mutual blood donation (FRMBD) and the effects of policy changes on blood donation. Design: This study is a cross-sectional review comparing the demographic characteristics of blood donors from 2017 to 2021. Setting and participants: The study included 1164 participants who were randomly sampled across China. The data were collected by trained staff and entered into a standard electronic data framework. Results: The number of blood donations observed in China generally increased from 2017 to 2021. Among the 1164 respondents, 785 were non-blood donors and 379 were blood donors. Most people's awareness of blood donation comes from organizations. Univariate analysis showed significant relationships between being a blood donor and being aged 30 or above ([Formula: see text], [Formula: see text]), being a doctor ([Formula: see text], [Formula: see text]), having Ph.D. degrees ([Formula: see text], [Formula: see text]), or being familiar with blood donation policy ([Formula: see text], [Formula: see text]). There was no significant difference in recognition between family FRMBD and voluntary non-remunerated blood donation (VNRBD). The study also investigated the impact of canceling FRMBD blood donation policies on the selection of blood donation methods. The results showed that the percentage of VNRBD was 57% and 41% in 2017 and 2021, respectively. This indicates that canceling FRMBD policies will not affect people's choice for blood donation methods. Conclusions: The results of the univariate analysis showed that people over 30 years of age, those with a Ph.D. or postgraduate degree, and those with knowledge of blood donation policies were more likely to be blood donors. People's reasons for banning the abolition of FRMBD may be due to the fact that it may not be possible to achieve an adequate supply of blood only through VNRBD. Through comparing the data of 2017 and 2021, it is found that the cancellation of the FRMBD blood donation policy will not have an impact on people's blood donation ways, and most people agree to cancel the FRMBD. Strengths and limitations of this study Strengths: This study analyzed factors related to decisions about blood donation in various regions of China. For the first time, we analyzed changes in perceptions of blood donation and donation rates before and after the abolition of FRMBD. • This survey did not record changes in the dynamics of the number of blood donations counted over consecutive years. • The individual donor factors such as gender and regional differences in blood donation awareness and facilities, which contribute to regional differences in people's blood donation behavior, were not investigated.